2017
DOI: 10.1038/s41598-017-04422-0
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced increased osteogenesis enables accelerated orthodontic tooth movement in ovariectomized rats

Abstract: As the number of elderly orthodontic patients increases, the impact of postmenopausal osteoporosis on orthodontic tooth movement (OTM) has attracted a great deal of attention because OTM relies on alveolar bone remodeling. The question of whether OTM causes subsequent alveolar bone loss and is harmful to alveolar bone health under osteoporotic conditions remains to be answered. The present study aimed to clarify the influences of OTM on alveolar bone in osteoporotic rats. OTM was accelerated in ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…However, the mechanism of orthodontic force-induced bone formation at the tension site of a moved tooth is unclear. Our results showed that proper mechanical loading significantly increased levels of ALP and osterix-positive cells, which is consistent with previous studies (Fu et al 2016 ; Dai et al 2017 ). Additionally, mechanical loading obviously increased bone volume at tension sites in the rat tooth movement model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the mechanism of orthodontic force-induced bone formation at the tension site of a moved tooth is unclear. Our results showed that proper mechanical loading significantly increased levels of ALP and osterix-positive cells, which is consistent with previous studies (Fu et al 2016 ; Dai et al 2017 ). Additionally, mechanical loading obviously increased bone volume at tension sites in the rat tooth movement model.…”
Section: Discussionsupporting
confidence: 93%
“…However, mechanical stimulation not only directly affects bone homeostasis by stimulating osteoclastogenesis, but also has positive effects on osteoblastogenesis. Recent studies demonstrated that marked upregulation of bone formation from increased osteoblast activity was a common feature of OTM at tension sites (Fu et al 2016 ; Kariya et al 2015 ; Liu et al 2017a , b , c ; Dai et al 2017 ). However, the mechanism of orthodontic force-induced bone formation at the tension site of a moved tooth is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…After M1 extraction, the animals were given four‐week tissue healing period (the optimal period as determined in the ABR experiment), OTM was applied to the upper left second molar (M2) for 2 and 3 weeks ( n = 11 for test and control at each OTM time point). The orthodontic model was performed as detailed previously with some modifications . In brief, the mice were anesthetized with IP injection of ketamine and xylazine (9:1, respectively) and a 3 mm nickel‐titanium closed coil spring (TOMY International, Tokyo, Japan) (10 g of constant force), was inserted between the upper incisors and the M2 for 2 or 3 weeks, thereby moving M2 into the ABR site.…”
Section: Methodsmentioning
confidence: 99%
“…The orthodontic model was performed as detailed previously with some modifications. 15,22 In brief, the mice were anesthetized with IP injection of ketamine and xylazine (9:1, respectively) and a 3 mm nickel-titanium closed coil spring (TOMY International, Tokyo, Japan) (10 g of constant force), was inserted between the upper incisors and the M2 for 2 or 3 weeks, thereby moving M2 into the ABR site. To enhance the attachment of the ligature to the teeth, a 0.1 mm stainless wire was inserted into a shallow groove drilled at the incisor tooth cervix (approximately 0.5 mm from the gingiva) and fixed with dental self-adhesive resin cement (RelyX TM U200,3 M, Maplewood, MN).…”
Section: Otm Into Regenerated Site Modelmentioning
confidence: 99%
See 1 more Smart Citation